ANALISIS WATER BALANCING PRIMARY LOOP CHILLER SYSTEM TERHADAP COP (Coefficient Of Performance) - Komarudin, Komarudin; Manik, Ida El Methelina (Bina Teknika, 2018)
Water is one of the major media for heat transfer process in the cooling system. The size of the flow rate of water entering the system will affect the overall cooling. Analysis of water balancing primary loop chiller system against COP (Coefficient Of Performance) is based on the observation the performance of the chiller system during operational with temperature of chilled water produced that not able to achieve the desired criteria when demand for chilled water increasing. After analysis conducted, it is known that decreasing efficiency of cooling system caused by uncontrolled water flow rate into the system. After water balancing is done, the flow rate of the water coming into the system (evaporator) can be controlled by using the balancing valve so that the flow rate increased from 16.07 x 10-3 m3 / s to 52.70 x 10-3 m3 / s, resulting in increased chiller COP value system from 2.4 to 4.1.